The hydrodynamic performance of a tension leg platform with one-tendon failure. (4th July 2019) - Qi, Yinghe; Tian, Xinliang; Guo, Xiaoxian; Lu, Haining; Liu, Lei
ABSTRACT: As one of the most widely used types of deepwater offshore platforms, the Tension Leg Platform (TLP) has shown excellent motion performance in waves; however, a detailed evaluation of their performance under tendon failure condition is vital and necessary. In this study, numerical simulations were conducted in both time and frequency domains using the commercial software HydroD and OrcaFlex, respectively. The numerical results were validated by a series of wave basin model tests. The motions of the TLP, with one tendon failure, and loads on the effective tendons, were studied in dynamic analyses to evaluate the potential adverse impact of tendon failure. Moreover, sensitivity studies of TLP performance under tendon failure were also conducted with various quantities of hull ballast. The relation between the response of the TLP and quantities of ballast were established and some advices were provided about lowering the risks of the loss of TLP stability under one-tendon failure condition.